Analisis Sistem Akuntansi Persediaan Barang Pada PT. Bumi Teknik Semesta - Gian Afianita Shalshabila; Ardiansyah (PT. Karya Inovatif Nusantara, 2024)
This study aims to analyze the inventory accounting system at PT Bumi Teknik Semesta, a company facing significant challenges in inventory management. These challenges include reliance on manual recording methods, frequent overstock and stockout issues caused by discrepancies between computer data and physical stock, and the lack of employee training on inventory procedures. This research adopts a case study approach, utilizing secondary data analysis and interviews with employees involved in inventory recording processes. The findings reveal that manual recording methods lead to data inaccuracies, which disrupt inventory availability. Moreover, the lack of employee training exacerbates inefficiencies in inventory management. This study recommends implementing a computerized flowchart to replace the manual method. The implications of this research suggest that the company can adopt the proposed system to improve data accuracy, streamline processes, and address persistent overstock and stockout problems effectively